Modular organization of the catalytic center of RNA polymerase - Mustaev, Arkady (The National Academy of Sciences of the USA, 1997)
The Fe(2+) ion that specifically replaces Mg(2+) in the active center of RNA polymerase generates reactive hydroxyl radicals that cause highly localized cleavage of polypeptide chains. Mapping of the cleavage sites revealed the overall architecture of the active center. Nine distinct sites, five in the β subunit and four in the β′ subunit of Escherichia coli RNA polymerase, all at or near highly conserved sequence motifs, are brought together in the enzyme’s ternary structure within the distance of ≈1 nm from the active center Me(2+). These sites are located in at least six different domains of the subunits, reflecting modular organization of the active center.